Missense Mutations in Desmoplakin Plakin Repeat Domains Have Dramatic Effects on Domain Structure and Function - Mohammed, Fiyaz; Odintsova, Elena; Chidgey, Martyn (International journal of molecular sciences, 2022)
Plakin repeat domains (PRDs) are globular modules that mediate the interaction of plakin proteins with the intermediate filament (IF) cytoskeleton. These associations are vital for maintaining tissue integrity in cardiac muscle and epithelial tissues. PRDs are subject to mutations that give rise to cardiomyopathies such as arrhythmogenic right ventricular cardiomyopathy, characterised by ventricular arrhythmias and associated with an increased risk of sudden heart failure, and skin blistering diseases. Herein, we have examined the functional and structural effects of 12 disease-linked missense mutations, identified from the human gene mutation database, on the PRDs of the desmosomal protein desmoplakin. Five mutations (G2056R and E2193K in PRD-A, G2338R and G2375R in PRD-B and G2647D in PRD-C) rendered their respective PRD proteins either fully or partially insoluble following expression in bacterial cells. Each of the residues affected are conserved across plakin family members, inferring a crucial role in maintaining the structural integrity of the PRD. In transfected HeLa cells, the mutation G2375R adversely affected the targeting of a desmoplakin C-terminal construct containing all three PRDs to vimentin IFs. The deletion of PRD-B and PRD-C from the construct compromised its targeting to vimentin. Bioinformatic and structural modelling approaches provided multiple mechanisms by which the disease-causing mutations could potentially destabilise PRD structure and compromise cytoskeletal linkages. Overall, our data highlight potential molecular mechanisms underlying pathogenic missense mutations and could pave the way for informing novel curative interventions targeting cardiomyopathies and skin blistering disorders.